Analisis Semantik Kata Rizq Karim dalam Al-Qur'an - Ahmad Qhodiri; Bashori (Rahmad : Jurnal Studi Islam dan Ilmu Al-Qur'an, 2025)
This article examines the semantic meaning of the phrase rizq karīm in the Qur'an using a qualitative approach and semantic analysis method. The term rizq karīm is a linguistic expression that carries theological and moral values in the Qur'an and appears in six verses across various surahs. This study aims to explore the lexical and contextual depth of this phrase and to identify those who, according to the Qur'an, are entitled to receive this noble provision. Data were collected through library research on Qur’anic verses containing rizq karīm, supported by references from classical and contemporary tafsir works as well as Arabic linguistic literature. The findings reveal that rizq karīm encompasses both material and spiritual provisions, covering worldly and hereafter rewards, granted to those who have faith, perform righteous deeds, migrate for God’s cause, strive in His path, and uphold piety and noble character. Exegetes such as al-Ṭabarī, Ibn ‘Āshūr, and al-Ṭabāṭabā’ī interpret rizq karīm as paradise the ultimate and eternal form of provision while others like al-Ālūsī and al-Ṭabrisī describe it as an exalted, high-quality, and pleasing form of sustenance. Quraish Shihab offers a broader interpretation, emphasizing that karīm denotes the best quality according to its object, and that rizq karīm includes all forms of divine blessings that are perfect and satisfying. This study underscores the importance of semantic analysis in uncovering the multidimensional meanings of Qur’anic terminology.